Potensi Ekstrak Jahe Gajah (Zingiber officinale var. Roscoe) Sebagai Bahan Aktif Sediaan Gargarisma dalam Mencegah Pertumbuhan Streptococcus mutans Penyebab Karies Gigi - Asmawati; Gunawan, Muh. Arfandy; Setiawan Jumain, Muhammad Asman; Dewi, Ratnasari (Jurusan Farmasi Poltekkes kemenkes Makassar, 2024)
Potential of Elephant Ginger Extract (Zingiber officinale var. Roscoe) as an active ingredient in Gargarisma preparation in inhibiting the growth of Strptococcus mutans which causes dental caries Ginger plants are known to contain chemical compounds in the form of phenols and flavonoids where these compounds have potential antibacterial power. This study aims to formulate elephant ginger extract into gargarisma preparations and determine the stability of the physical quality as well as to determine the antibacterial potential of gargarisma elephant ginger extract preparations optimally. Elephant ginger was extracted using the maceration method, then dried using a freeze-drying device. Then formulation into gargarisma preparations whit concentrations of 5%, 10%, and 20% elephant ginger extract followed by evaluation of the preparation including pH test, organoleptic test, and viscosity test as well as antibacterial power test. The results of each study have an average value before and after the Cycling test, namely the pH test with 5% concentration: 6.13 and 6.06; concentration 10%: 5.92 and 5.96; concentration 20%: 5.96 and 5.91, on the viscosity test 5% concentration: 1.86cps and 2.19cps; concentration 10%: 2.05cps and 2.45cps; concentration 20%: 2.55cps and 3.06cps, the organoleptic test did not change. From the results of the inhibition test, the average value was obtained at a concentration of 5%: 9mm; concentration 10%: 14.33mm; concentration 20%: 17.67mm. it can be concluded that 5%, 10%, and 20% concentrated ginger extract can be formulated into elephant ginger preparations with gargarisma constraint and fulfils the physical quality requirements of gargarisma preparations as well as for the antibacterial power test, the significance value (p<0,05) indicates a significant difference. Each concentration. At a concentration of 10%, it had an optimal effect in inhibiting the growth of Streptococcus mutans. Tanaman Jahe Gajah diketahui mengandung senyawa kimia berupa fenol, flavonoid dimana senyawa tersebut memiliki potensi daya antibakteri. Penelitian ini bertujuan untuk memformulasi ekstrak jahe gajah menjadi sediaan gargarisma dan mengetahui stabilitas mutu fisik serta untuk mengetahui potensi antibakteri dari sediaan gargarisma ekstrak jahe gajah secara optimal. Jahe gajah diekstraksi menggunakan metode maserasi, kemudian dikeringkan menggunakan alat freeze drying, lalu diformulasi menjadi sediaan gargarisma dengan konsentrasi ekstrak jahe gajah 5%, 10%, dan 20% dilanjutkan dengan evaluasi sediaan meliputi uji pH, uji organoleptik, dan uji viskositas serta uji daya antibakteri. Hasil penelitian masing-masing memiliki nilai rata-rata sebelum dan sesudah Cycling test yaitu pada uji pH konsentrasi 5%: 6,13 dan 6,06; konsentrasi 10%: 5,92 dan 5,96; konsentrasi 20%: 5,96 dan 5,91, pada uji viskositas konsentrasi 5%: 1,86cps dan 2,19cps; konsentrasi 10%: 2,05cps dan 2,45cps; konsentrasi 20%: 2,55cps dan 3,06cps, pada uji organoleptik tidak mengalami perubahan. Dari hasil pengujian daya hambat didapatkan nilai rata-rata pada konsentrasi 5%: 9mm, konsentrasi 10%: 14,33mm, konsentrasi 20%: 17,67mm. Dapat disimpulkan bahwa ekstrak jahe gajah dengan konsentrasi 5%, 10%, dan 20% dapat diformulasi menjadi sediaan gargarisma dan memenuhi syarat mutu fisik sediaan gargarisma serta untuk uj daya antibakteri diperoleh nilai Signifikansi (p<0,05) menunjukkan adanya perbedaan yang bermakna tiap konsentrasi. Pada konsentrasi 10% sudah memberikan efek yang optimal dalam menghambat pertumbuhan Streptococcus mutans.